Design of fins with a grooved heat pipe for dissipation of heat from high-powered automotive LED headlights. (15th January 2019) - Huang, De-Shau; Chen, Tzu-Ching; Tsai, Liang-Te; Lin, Ming-Tzer
Highlights: An effective heat dissipation module with a heat pipe is applied into the high-power LED headlights. Experiments and numerical simulation of heat dissipation are validated. Heat dissipation performance on temperature distribution of a high-power LED headlight is evaluated. AlN substrate with a heat pipe most effectively dissipates heat from LED headlights. Abstract: Despite the widespread use of high-powered LED lights in the automotive industry, it was found that difficulties in the dissipation of heat can lead to high LED operating temperatures, which can be detrimental in terms of the LED's brightness and lifespan. In this study, we sought to enhance the heat transfer efficiency of LED by incorporating fins with a grooved heat pipe on the heat sink. ANSYS Fluent software is used to model the heat transfer mechanisms in order to optimize the heat pipe parameters and fin design with the aim of maintaining the LED chip temperature within a safe operating range. The temperature distributions of LED headlights are simulated for different materials of the heat sink and the printed circuit board (PCB), and fin designs with a heat pipe. In the study, it was found that an increase in the thermal conductivity coefficient of the substrate resulted in a decrease in the LED junction temperature; however, higher thermal efficiency was not necessarily sufficient. The proposed model showed that the integration of 76-mm-long grooved heat pipes with an effective thermal conductivity of 6000 W/(m·K) and 2-mm prolonged plate heat dissipation fins on the heat sink with an AlN Ceramic having a 180 W/(m·K) proved effective in dissipating heat from high-powered LED headlights within a highly constrained space.